Valiant defender - McCoy, Shirlee (McCoy, Shirlee. Military K-9 unit., 2018)
After relentless searching, Captain Justin Blackwoods closing in on the Red Rose Killer. But when his daughter becomes a target, the hunt turns personal. With the help of his new partner, Captain Gretchen Hill, and his K-9, Quinn, Justin will race to save his daughter and bring down his nemesis once and for allor die trying.